The effect of slurry type on drilled shaft cover quality. Issue 2 (6th April 2017) - Mobley, S.; Costello, K.; Mullins, G.
Abstract : Until recently, concrete flow in tremie-placed drilled shafts has been mischaracterised as rising uniformly with laitance formation occurring at the top of the shaft. In actuality, concrete first fills a portion of the reinforcement cage before flowing radially to the cover region. Depending on slurry type, the radial flow can produce laitance-filled creases/channels that project the reinforcing cage configuration to the side of shaft surface. The flow pattern (and creases) can affect filter cake thickness, cover quality and propensity for corrosion. This paper examines 24 tremie-placed laboratory drilled shaft specimens, constructed using bentonite, polymer or natural slurry to identify correlations between slurry type and laitance channel formation. The extent of the laitance channel effects was quantified with surface texture, corrosion potential and strength distribution methods. A direct correlation between the use of bentonite slurry and laitance channel formation was identified which showed a high propensity for corrosion and lower strengths. Shafts cast using polymer behaved the same as the shafts cast using water, neither of which showed a heightened propensity for corrosion or reduction in strength.